Existence of High Temperature Geothermal Resources in the Igneous Rock Regions of South China - Li, Yiman; Tian, Jiao; Cheng, Yuanzhi; Jiang, Guangzheng; Zhang, Ying; Chen, Kai; Pang, Zhonghe (Frontiers in Earth Science, 2021)
Large areas of Yanshan period granites with high heat production values (3–10 μW/m3) and mantle plume around Hainan province co-exist in Igneous Rocks Regions of South China (IRRSC). Surface manifestations are mainly warm/hot springs with temperatures below 90 °C and no typical phenomenon of high temperature resources have been observed. The main objective of this paper is to discuss the existence of high temperature geothermal resources and their possible locations under this kind of geothermal and tectonic background by analysis of high temperature heat sources, borehole temperature measurement, and reservoir temperature estimation. Two possible partial melts of the magma chamber were detected as high temperature heat sources in the Southern Leizhou Peninsular and North Hainan Island at a depth of 8–15 km. Other low resistivity zones in the upper crust are more likely caused by fluid in the formations or faults but not high temperature heat sources. This was also verified by borehole temperature measurement in these two areas, with maximum formation temperatures of 211°C and 185°C found, respectively. Reservoir temperatures from fluid geothermometers show lower temperatures of between 110–160°C for typical geothermal fields over the IRRSC but not in the Southern Leizhou Peninsular and Northern Hainan Island. In all, high temperature geothermal resources may be found in the Southern Leizhou Peninsular and on Northern Hainan Island.